Chinese speakers' language use in classroom discussion and oral presentation - Hii, Yu Ching (University Malaysia Sarawak, UNIMAS., 2009)
The study is to investigate the language use among the Chinese speakers in the classroom discussion and oral presentation. This study focuses on two objectives. The first objective is to figure out the frequently use and less frequently use language among the Chinese speakers in their classroom discussion and oral presentation. Secondly, the researcher intended to examine the functions of language in classroom discussion and oral presentation. Hence, ten Chinese speakers of TESL in UNIMAS are identified to be the participants in this study. These participants are randomly chosen by the researcher. This study used qualitative method in collecting the data. Audio-recordings of the classroom discussions and oral presentations are collected throughout the whole research. Besides, a semi-structured interview is used in the study to add on the background information of the participants on their language repertoire and reasons for choosing the language in the particular social context. The framework proposed by Halliday (1978), Halliday and Hassan (1985), and Black (1995) on the functions of language is used in analyzing the data for the second objective. From the findings, the frequently use language in the classroom discussion was English and followed by Mandarin. The results showed that Chinese speakers tend to use English in their oral presentation. As for the findings for functions of language, informative and heuristic are more preferable in the classroom discussion while the Chinese speakers use language for informative in the oral presentation. Thus, this study is focusing on Chinese speakers’ type of language use and the purpose of the language in the classroom discussion and oral presentation.